Spectrum of chronic lung allograft pathology in a mouse minor‐mismatched orthotopic lung transplant model. Issue 1 (29th November 2018) - Martinu, Tereza; Oishi, Hisashi; Juvet, Stephen C.; Cypel, Marcelo; Liu, Mingyao; Berry, Gerald J.; Hwang, David M.; Keshavjee, Shaf
Abstract : Chronic lung allograft dysfunction (CLAD) is a fatal condition that limits survival after lung transplantation (LTx). The pathological hallmark of CLAD is obliterative bronchiolitis (OB). A subset of patients present with a more aggressive CLAD phenotype, called restrictive allograft syndrome (RAS), characterized by lung parenchymal fibrosis (PF). The mouse orthotopic single LTx model has proven relevant to the mechanistic study of allograft injury. The minor‐alloantigen‐mismatched strain combination using C57BL/10(B10) donors and C57BL/6(B6) recipients reportedly leads to OB. Recognizing that OB severity is a spectrum that may coexist with other pathologies, including PF, we aimed to characterize and quantify pathologic features of CLAD in this model. Left LTx was performed in the following combinations: B10→B6, B6→B10, B6→B6. Four weeks posttransplant, blinded pathologic semi‐quantitative assessment showed that OB was present in 66% of B10→B6 and 30% of B6→B10 grafts. Most mice with OB also had PF with a pattern of pleuroparenchymal fibroelastosis, reminiscent of human RAS‐related pathology. Grading of pathologic changes demonstrated variable severity of airway fibrosis, PF, acute rejection, vascular fibrosis, and epithelial changes, similar to those seen in human CLAD. These assessments can make the murine LTx model a more useful tool for further mechanistic studies of CLAD pathogenesis. Abstract : In this article, the authors present a detailed assessment and semiquantitative scoring of chronic pathology in the minor‐mismatched mouse lung transplant model, showing important parallels to human chronic lung allograft histopathology and dysfunction.